Bond strength of resin cements to leucitereinforced ceramics - Rubens Nazareno Garcia; Reinaldo Francisco do Nascimento; Ana Cristina Rocha Gomes; Marcelo Giannini; Luiz Carlos Machado Miguel; Peter Clayton Moon (Revista Sul-Brasileira de Odontologia, 2013)
The aim of this study was to evaluate the shear bond strength (SBS) of two resin cements to four leucite-reinforced ceramics. Material and methods: Forty ceramic blocks (4 mm wide, 14 mm length and 2 mm thick) were used and the samples abraded with aluminum oxide (90 µm). The samples were divided into eight groups (n = 5). Two resin cements (conventional RelyX ARC and self-adhesive RelyX U100 – 3M ESPE) were bonded to Creapress (CRE-Creation/Klema), Finesse All-Ceramic (FIN-Dentsply/ Ceramco), IPS Empress Esthetic (IEE-Ivoclar Vivadent) and Vita PM9 (PM9- Vita). For all groups and in each ceramic block, after application of 10% hydrofluoric acid and silanation, three Tygon tubings were positioned over the ceramics, which were filled in with the resin cements (light-cure for 40 s). The tubings were removed to expose the specimens in format of cylinders (area: 0.38 mm2) and samples were stored in relative humidity at 24±2 °C for one week. After this period, each sample was attached to testing machine and the specimens were submitted to shear bond test (applied at the base of the specimen/cement cylinder with a thin wire/0.2 mm) at speed of 0.5 mm/ min, until failure. The results were analyzed by two-way ANOVA (resin cements and ceramic systems) and Tukey test (p<0.05). Results: The means (SD) were (in MPa): ARC + CRE = 32.1±4.3; ARC + FIN = 28.3±3.7; ARC + IEE = 25.9±4.4; ARC + PM9 = 22.2±2.1; U100 + CRE = 38.0±5.2; U100 + FIN = 36.9±2.8; U100 + IEE = 38.4±2.9; U100 + PM9 = 34.3 ±7.3. U100 showed higher SBS to ceramics than ARC. U100 had higher SBS when applied on IEE ceramic than on PM9. For ARC, SBS obtained with CRE was higher than with IEE and PM9. Conclusion: RelyX U100 can provide higher SBS to leucite-reinforced ceramics than conventional resin cement. The resin cements applied on the PM9 ceramic surface resulted in lower SBS.